Metabolic power responses to different small sided games in football and futsal players - Kose, M. G.; Hazir, T.; Kin-Isler, A. (International Journal of Performance Analysis in Sport, 2023)
This study was designed to examine the metabolic power (MP) responses of football and futsal players to different small sided games (SSG). Twelve football and 12 futsal players participated in this study voluntarily. Maximal oxygen consumption(VO2max) and coach scoring (CS) were used for SSG player matching. Football and futsal players participated in two bouts of 2vs2, 3vs3 and 4vs4-SSG in random order. Kinematic and MP variables during SSG were measured by using GPS. To determine the effects of branch and SSG on each dependent variable of total distance (TD), relative TD (TDRel), MPaverage, relative TD in four different MP levels, and negative and positive acceleration numbers, a main effects 2-way analysis of variance with Bonferroni post hoc was used. MPaverage was significantly higher in futsal players compared to football players (p = 0.000). TD (p = 0.000) and TDRel(p = 0.013) of futsal players was significantly higher compared to football players. Total deceleration and acceleration numbers during SSG were significantly higher for futsal players than football players (p = 0.026). MP requirements were independent of the game format (p > 0.05), except for 2vs2-SSG (p < 0.05), when the playing area per player was kept constant. The results of this study showed that external load indicators during SSG were higher in futsal players compared to football players.